2023
DOI: 10.3390/ijms24097705
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Six Waxy Components in Summer Black Grapes (Vitis vinifera) and Mancozeb and Its Effect on the Residue of Mancozeb

Abstract: Mancozeb, an antifungal typically used for the growth of fruits, has the characteristic of non-internal absorption, and has a risk of binding to the waxy components of fruits. This work investigated the interaction of pesticide molecules with the waxy layer on the grape surface and their effects on pesticide residues in grapes. The study observed significant changes in the compositions of the waxy layer on the grape surface after soaking in a mancozeb standard solution. The six substances—oleanolic acid, ursol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Biomimetic autocrine waxy materials (AWMs), inspired by the renewable solid epidermal waxes of terrestrial plants, are attracting increasing attention. Scientists have found that the waxy layer is an organic mixture consisting mainly of C 20 -C 34 aliphatic substances , and usually exhibits hydrophobic properties. , By mimicking the waxy layer in leaves, Wang et al reported a solid organogel material with a regenerable sacrificial alkane surface layer and demonstrated an important role in combating solid deposition . Some scholars have exploited the rapid autocrine ability and hydrophobicity of AWMs, and the as-prepared materials quickly and spontaneously recovered their superhydrophobicity even after being subjected to severe plasma etching .…”
Section: Introductionmentioning
confidence: 99%
“…Biomimetic autocrine waxy materials (AWMs), inspired by the renewable solid epidermal waxes of terrestrial plants, are attracting increasing attention. Scientists have found that the waxy layer is an organic mixture consisting mainly of C 20 -C 34 aliphatic substances , and usually exhibits hydrophobic properties. , By mimicking the waxy layer in leaves, Wang et al reported a solid organogel material with a regenerable sacrificial alkane surface layer and demonstrated an important role in combating solid deposition . Some scholars have exploited the rapid autocrine ability and hydrophobicity of AWMs, and the as-prepared materials quickly and spontaneously recovered their superhydrophobicity even after being subjected to severe plasma etching .…”
Section: Introductionmentioning
confidence: 99%